[Making tortillas] - Rafael Antolino::::::photographer::: (2005)
Description supplied by photographer: "Mi primo haciendonos tortillas porque teníamos tanta hambre que decidimos a ponernos a hacer tortillas solos." Translation of description: "My cousin is making tortillas for us to eat. We were hungry so we though to make tortillas on our own."